MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN METODE LATIHAN BERSTRUKTUR DALAM MATERI LARUTAN PENYANGGA SISWA KELAS XI IPA 1 SMA NEGERI 6 BANJARMASIN - Soraya Alwarizna; Parham Saadi; Rusmansyah Rusmansyah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. A research has been done about the use of structured exercises method to improve students’ activity and learning outcomes in class XI IPA 1 SMAN 6 Banjarmasin on the buffer solution material. This research aims to determine the activity of the teacher, students’ activities and learning outcomes in learning buffer solution material by using structured exercise method. This study uses classroom action research design with 2 cycles. First cycle consists of 3 meetings and second cycle consists of 1 meeting. The subjects of the research were students of XI IPA 1 SMAN 6 Banjarmasin, there were 35 students consist of 10 male students and 25 female students. The data collection techniques uses engineering test and non-engineering test. The data analysis uses percentage technique. The results show that by using structured exercise method in teaching buffer solution material can increase the activity of teachers and students in the learning process. Student learning outcomes in the materials of the buffer solution by using structured exercise method increased from an average of 35.12% on the pretest to 74.42% in the first cycle and a 86.54% in the second cycle.Keywords : learning methods, structured exercise, buffer solution.